2013
DOI: 10.1007/s11556-013-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

Training effects on motor–cognitive dual-task performance in older adults

Abstract: This systematic review investigated whether healthy older adults benefit from training interventions in motor-cognitive dual-task (DT) situations and which specific aspects of the intervention and/or task selection contribute to training benefits. Training effects were analysed with regard to the training programme (e.g., general ST or DT training) and task conditions (e.g., standing or walking, complexity of secondary cognitive task). Literature was searched via OVIDsp (Medline, EMBASE, PsycINFO). DT studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 103 publications
8
159
3
5
Order By: Relevance
“…Moreover, according to evidence that motor and cognitive benefits at old age may be obtained by means of DT training with a certain level of task specificity and rising difficulty [15], further DT experiences with such characteristics were embedded in the exercise training of the experimental group. Task specificity was ensured using functional mobility tasks common in everyday life, as walking on uneven or narrow surface, or carrying objects, walking while talking, or picking up objects off the floor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, according to evidence that motor and cognitive benefits at old age may be obtained by means of DT training with a certain level of task specificity and rising difficulty [15], further DT experiences with such characteristics were embedded in the exercise training of the experimental group. Task specificity was ensured using functional mobility tasks common in everyday life, as walking on uneven or narrow surface, or carrying objects, walking while talking, or picking up objects off the floor.…”
Section: Methodsmentioning
confidence: 99%
“…There is consistent evidence that both physical and cognitive training have the potential to maintain cognitive efficiency in aging [11] and that combining them in successive or simultaneous way amplifies their efficacy [12, 13]. For this reason, physical-cognitive dual tasking is emerging as a novel modality for reaping largest cognitive health benefits [14, 15]. In their review, Wollesen and Voelcker-Rehage [15] highlighted the beneficial effects of locomotor-cognitive DT training for gait and posture performance and for processing speed and executive function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our statistical analysis focused exclusively on gait speed, and we included only studies that measured unobstructed dual-task walking in order to maximize homogeneity for comparison. It is possible that the interventions in the included (and some excluded) studies may have demonstrated significant effects on gait in other everyday mobility tasks (e.g., transfers or negotiating obstacles), but these have been considered in other reviews [6,13,14] . There remains a limited number of well-conducted trials examining treatment-related effects of other gait parameters during dual-task walking.…”
Section: Limitationsmentioning
confidence: 99%
“…Apparently, this performance is highly developable in subjects with different chronic conditions ) than healthy elderly ; nevertheless, it appears that only few studies investigated appropriate physical activity interventions to improve dual tasking. Besides, it has to be considered a non-secondary aspect; exercise interventions and testing procedures were extensively different between the few trials reported by the literature (Wollesen and Voelcker-Rehage 2013).…”
Section: Introductionmentioning
confidence: 99%